An electrochemical approach to graphene oxide coated sulfur for long cycle life. Issue 31 (21st July 2015) - Moon, Joonhee; Park, Jungjin; Jeon, Cheolho; Lee, Jouhahn; Jo, Insu; Yu, Seung-Ho; Cho, Sung-Pyo; Sung, Yung-Eun; Hong, Byung Hee
Abstract : Owing to the possibilities of achieving high theoretical energy density and gravimetric capacity, sulfur has been considered as a promising cathode material for rechargeable lithium batteries. Abstract : Owing to the possibilities of achieving high theoretical energy density and gravimetric capacity, sulfur has been considered as a promising cathode material for rechargeable lithium batteries. However, sulfur shows rapid capacity fading due to the irreversible loss of soluble polysulfides and the decrease in active sites needed for conducting agents. Furthermore, the low electrical conductivity of sulfur hampers the full utilization of active materials. Here we report that graphene oxide coated sulfur composites (GO-S/CB) exhibit improved electrochemical stability as well as enhanced rate performance, evidenced by various electrochemical analyses. The cyclic voltammetry and the galvanostatic cycling analysis revealed that the GO plays key roles in homogenizing the nanocomposite structures of the electrodes, in improving the electrochemical contact, and in minimizing the loss of soluble polysulfide intermediates. An electrochemical impedance spectroscopy analysis also confirms the enhanced structural stability of the GO-S/CB composites after battery operation. As a result, the GO-S/CB exhibited excellent cycle stability and specific capacity as high as ∼723.7 mA h g −1 even after 100 cycles at 0.5 C.